Впровадження відновлюваних джерел енергії у соціальну інфраструктуру. Огляд досліджень. - Dranik, Maksym (General Energy Institute of the National Academy of Sciences of Ukraine, 2025)
The article examines the integration of renewable energy sources (RES) into Ukraine’s social infrastructure as a key factor in ensuring energy independence, the stable functioning of public institutions, and achieving sustainable development goals. In light of current challenges − particularly the ongoing war, widespread infrastructure damage, and energy instability − special emphasis is placed on the urgent need for decentralized energy supply and a transition to environmentally friendly energy sources. The study examines the potential for utilizing solar, wind, bioenergy, and geothermal resources in educational institutions, healthcare facilities, social services, and administrative and municipal establishments. The article also outlines the main technical, organizational, and economic aspects of RES integration into the social infrastructure. It presents an overview of current legislation, as well as national and international funding programs that support such initiatives. Furthermore, particular attention is given to the analysis of successful case studies of energy efficiency projects implemented at the local community level. The study identifies key barriers hindering the widespread adoption of renewable technologies, including insufficient technical preparedness of facilities, lack of qualified personnel, limited awareness among local authorities, and difficulties in accessing financial resources. As a result, the research justifies the need for a comprehensive strategy for renewable energy deployment in the social sector, taking into account both national priorities and regional specifics. The paper concludes with practical recommendations for integrating RES into local-level energy policies in Ukraine.Keywords: renewable energy, social infrastructure, decentralization of electricity supply, energy efficiency, energy security, sustainable development.